Characterizing Atmospheric Transport Pathways to Antarctica and the Remote Southern Ocean Using Radon-222 - Chambers, Scott D.; Preunkert, Susanne; Weller, Rolf; Hong, Sang-Bum; Humphries, Ruhi S.; Tositti, Laura; Angot, Hélène; Legrand, Michel; Williams, Alastair G.; Griffiths, Alan D.; Crawford, Jagoda; Simmons, Jack; et al. (Frontiers in Earth Science, 2018)
We discuss remote terrestrial influences on boundary layer air over the Southern Ocean and Antarctica, and the mechanisms by which they arise, using atmospheric radon observations as a proxy. Our primary motivation was to enhance the scientific community’s ability to understand and quantify the potential effects of pollution, nutrient or pollen transport from distant land masses to these remote, sparsely-instrumented regions. Seasonal radon characteristics are discussed at 6 stations (Macquarie Island, King Sejong, Neumayer, Dumont d’Urville, Jang Bogo and Dome Concordia) using 1-4 years of continuous observations. Context is provided for differences observed between these sites by Southern Ocean radon transects between 45-67S made by the Research Vessel Investigator. Synoptic transport of continental air within the marine boundary layer (MBL) dominated radon seasonal cycles in the mid-Southern Ocean site (Macquarie Island). MBL synoptic transport, tropospheric injection, and Antarctic outflow all contributed to the seasonal cycle at the sub-Antarctic site (King Sejong). Tropospheric subsidence and injection events delivered terrestrially-influenced air to the Southern Ocean MBL in the vicinity of the circumpolar trough (or “Polar Front”). Katabatic outflow events from Antarctica were observed to modify trace gas and aerosol characteristics of the MBL 100-200 km off the coast. Radon seasonal cycles at coastal Antarctic sites were dominated by a combination of local radon sources in summer and subsidence of terrestrially-influenced tropospheric air, whereas those on the Antarctic Plateau were primarily controlled by tropospheric subsidence. Separate characterization of long-term marine and katabatic flow air masses at Dumont d’Urville revealed monthly mean differences in summer of up to 5 ppbv in ozone and 0.3 ng m-3 in gaseous elemental mercury. These differences were largely attributed to chemical processes on the Antarctic Plateau. A comparison of our observations with some Antarctic radon simulations by global climate models over the past two decades indicated that: (i) some models overestimate synoptic transport to Antarctica in the MBL, (ii) the seasonality of the Antarctic ice sheet needs to be better represented in models, (iii) coastal Antarctic radon sources need to be taken into account, and (iv) the underestimation of radon in subsiding tropospheric air needs to be investigated.